2017
DOI: 10.5958/0975-6906.2018.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic relationship between restorer genes for A1 and A4 CMS systems in pearl millet

Abstract: Understanding the allelic complementation of restoration among the stable restorer lines will contribute to robust pearl millet restorer breeding program. Thus, present study aimed to test allelic relationship between four diverse restorer lines each for A 1 and A 4 cytoplasmic male sterility (CMS) systems to find linkage between restorer genes carried by different restorers of each CMS systems. Six testcrosses were developed for each CMS system by crossing each of A 1 and A 4 male sterile lines (81A 1 and 81 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Gupta et al 2018 studied inheritance of fertility restoration for A 5 cytoplasm and reported trigenic inheritance of male fertility restoration, where dominant alleles at any two of the three duplicate complimentary loci will lead to fertility restoration. Govindaraj et al, 2018 reported allelic relationship between fertility restorer genes responsible for fertility restoration in A 1 and A 4 cytoplasm. Singhal et.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al 2018 studied inheritance of fertility restoration for A 5 cytoplasm and reported trigenic inheritance of male fertility restoration, where dominant alleles at any two of the three duplicate complimentary loci will lead to fertility restoration. Govindaraj et al, 2018 reported allelic relationship between fertility restorer genes responsible for fertility restoration in A 1 and A 4 cytoplasm. Singhal et.…”
Section: Resultsmentioning
confidence: 99%